Wave exciting force maximization of truncated cylinders in a linear array - Michailides, Constantine; Loukogeorgaki, Eva; Chatjigeorgiou, Ioannis K. (My University, 2020)
This study focuses on the determination of optimum layout configurations for a linear array of identical mutually interacting truncated cylinders. Optimum configurations correspond to those that maximize either the total heave exciting force acting on all cylinders of the array or the heave exciting force applied on pairs of cylinders within the array. For achieving this goal, we developed and applied an efficient optimization numerical process (ONP), where a robust hydrodynamic numerical model, capable of solving the diffraction problem of the examined multi-body arrangement in the frequency domain, was appropriately coupled with a genetic algorithm solver in an integrated computational environment. Initially, the efficiency of the ONP is demonstrated by comparing results with those of other investigations that resulted from the deployment of classical optimization methods. Then, ONP is applied for a linear array of nine cylinders for determining the optimum layout configurations under the action of the head and perpendicular to the array waves, and for different maximum allowable array lengths. The resulting optimum configurations correspond to a random positioning of the cylinders within the array. Nevertheless, they are characterized by the formation of clusters of closely-positioned cylinders, which induce positive hydrodynamic interactions in terms of maximizing the exciting forces.
Keywords: Hydrodynamic loads; Linear array; Optimization; Truncated cylinders; Wave diffraction; Wave-structure interaction